Bhs Inggris - Rahmatiah, Annanta Desi; Ainun, Hasbiah; Rokhimah, Rokhimah (Li Falah: Journal of Islamic Economics and Business, 2026)
This study aims to examine the effect of Customer Relationship Management (CRM) on customer loyalty, with trust as a mediating variable. A quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed, analyzed through SmartPLS software. A total of 100 respondents, selected through purposive sampling from customers of Rumah Makan Selera Rasa, served as the study sample. The results reveal that CRM exerts a positive and significant effect on customer loyalty, with a T-statistic value of 3.955 and a P-value of 0.000. Furthermore, CRM demonstrates a positive and significant influence on trust, with a T-statistic of 8.297 and a P-value of 0.000. Trust also exhibits a positive and significant effect on customer loyalty, with a T-statistic of 6.738 and a P-value of 0.000. Additionally, trust is confirmed to function as a significant mediating variable in the relationship between CRM and customer loyalty, with a P-value of 0.000. These findings indicate that the effective implementation of CRM in food service businesses can significantly enhance both customer trust and customer loyalty.